Electroluminescence efficiency enhancement in quantum dot light-emitting diodes by embedding a silver nanoisland layer - Yang, Xuyong (2015)
A colloidal quantum dot light-emitting diode (QLED) is reported with substantially enhanced electroluminescence by embedding a thin layer of Ag nanoislands into hole transport layer. The maximum external quantum efficiency (EQE) of 7.1% achieved in the present work is the highest efficiency value reported for green-emitting QLEDs with a similar structure, which corresponds to 46% enhancement compared with the reference device. The relevant mechanisms enabling the EQE enhancement are associated with the near-field enhancement via an effective coupling between excitons of the quantum dot emitters and localized surface plasmons around Ag nanoislands, which are found to lead to good agreement between the simulation results and the experimental data, providing us with a useful insight important for plasmonic QLEDs.